The Importance of the Solids Loading on Confirming the Dielectric Nanosize Dependence of BaTiO3 Powders by Slurry Method - Wei Zhou; Yi Mei Nie; Shu Jing Li; Hai Yan Liang (The Scientific World Journal)
The dielectric nanosize dependence of BaTiO3 powders was investigated by the slurry method, where two series of BaTiO3 slurries with 10 vol% and 30 vol% solids loadings were prepared as model samples. Applying the Bruggeman-Hanai equation, the high-frequency limiting permittivity (εh) of the slurries was extracted from the dielectric spectra. The εh of the 10 vol% slurry showed abnormal size independence in the range from 100 nm to 700 nm, and the εh of the 30 vol% slurry exhibited good agreement with the previous prediction. Through analysing quantitatively the response of εh to the changing permittivity of the powders under different solids loading, it was found that the εh of the slurry with lower solids loading is more inclined to be interfered by the systematic and random errors. Furthermore, a high permittivity value was found in the BaTiO3 powders with 50 nm particle size.